Transport-related experiences in China in response to the coronavirus (COVID-19) (2020)
In the year 2020, the Coronavirus (COVID-19) broke out in many countries of the world. In China, the Chinese government and people have adopted strong measures. After more than a month of fighting against the epidemic, the epidemic has been basically under control in China. However, in other countries of the world, such as South Korea, Japan, Iran, many countries in Europe, and the Americas, the epidemic is still developing rapidly and the situation is not optimistic. This paper summarizes the transport-related experience of China in the fight against the epidemic and hopes that it will be helpful to other countries in the fight against the epidemic. Keywords: transport; experience; coronavirus; epidemic